2015
DOI: 10.14260/jemds/2015/1017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antifungal Susceptibility Pattern of Candida SPP . Isolated From Clinical Specimens

Abstract: BACKGROUND:With the changing health scenario fungal infections have increased significantly, contributing to morbidity, mortality and health care cost. Candida is major human fungal pathogens that cause both superficial and deep tissue infections. With emergence of nonalbicans Candida species, availability of advanced identification methods and antifungal resistance, the spectrum of candidiasis has changed. OBJECTIVE: The aim of our study was to identify the distribution of Candida species among clinical isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…[6,12] In present study, C. albicans isolates had a 97.9% susceptibility to Amphotericin B, a polyene antifungal which was comparable to finding by Capoor et al [24]. In constrat to it, sagarika et al [25] and Mokadas et al [18] reported 100% susceptibility of C. albicans to Amphotericin B.…”
Section: Discussionsupporting
confidence: 87%
“…[6,12] In present study, C. albicans isolates had a 97.9% susceptibility to Amphotericin B, a polyene antifungal which was comparable to finding by Capoor et al [24]. In constrat to it, sagarika et al [25] and Mokadas et al [18] reported 100% susceptibility of C. albicans to Amphotericin B.…”
Section: Discussionsupporting
confidence: 87%
“…Over all resistance of Candida to Amphotericin B in the present study was 5.4%, which was comparable to other studies like study by Dharwad et al 13 and Sagarika Pradhan et al 12 where 8% and 6.4% resistance was reported respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The study by Dharwad et al 13 and Biradar et al 14 also had similar finding. The higher degree of resistance to fluconazole might be due to widespread and indiscriminate use of this drug for extended periods.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations